2018
DOI: 10.1002/eji.201747213
|View full text |Cite|
|
Sign up to set email alerts
|

Aberrant cell signalling in PBMCs upon IFN‐α stimulation in primary Sjögren's syndrome patients associates with type I interferon signature

Abstract: Primary Sjögren's syndrome (pSS) is a complex systemic autoimmune disease with heterogeneous disease manifestations. Genetic predisposition, hormonal and environmental factors are all thought to contribute to disease etiology and pathogenesis. A better understanding of the disease pathogenesis is required in order to establish new targeted therapies. We analysed MAPK/ERK and JAK/STAT signalling networks in peripheral blood mononuclear cells (PBMCs) upon stimulation with interferon alpha 2b (IFN-α2b) by flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
3
18
1
Order By: Relevance
“…Continuous activation and dysregulation of TLR and type I IFN signaling have been speculated to play a part in this signature and pathogenesis of autoimmune disease (29), and IFN signature positive pSS patients have been shown to have increased expression of TLR7 in certain cell types (30). In addition, we have previously shown that PBMC of pSS patients have an altered response to IFN-α stimulation (10). Hence we investigated cell signaling profiles in PBMC of pSS patients upon stimulation via TLR7 and −9, determined the gene expression profile of several IFN inducible genes and correlated these findings to plasma cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Continuous activation and dysregulation of TLR and type I IFN signaling have been speculated to play a part in this signature and pathogenesis of autoimmune disease (29), and IFN signature positive pSS patients have been shown to have increased expression of TLR7 in certain cell types (30). In addition, we have previously shown that PBMC of pSS patients have an altered response to IFN-α stimulation (10). Hence we investigated cell signaling profiles in PBMC of pSS patients upon stimulation via TLR7 and −9, determined the gene expression profile of several IFN inducible genes and correlated these findings to plasma cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from PBMC of 20 pSS patients and 17 healthy controls and transcribed into cDNA as described previously (10). The following Taqman gene expression assays were utilized: Hs00895608_m1 ( MxA ); Hs00973637_m1 ( OAS1 ); Hs00951349_m1 ( IFI44 ); Hs00977005_m1 ( GBP1 ); Hs00894837_m1 ( GBP2 ); Hs03928990_g1 (18S rRNA) (all Thermo Fisher Scientific, Waltham, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sjögren's syndrome is an autoimmune disease with glandular lymphocyte infiltration leading to symptoms of dry mouth and eyes, where approximately 50% of patients have a type I IFN signature (45,46). Given that this IFN signature is not present in all patients, one study analyzed the effects of IFN-a2b treatment of peripheral blood mononuclear cells (PBMCs) from patients with Sjögren's compared with PBMCs from healthy donors, including type I IFN signature-positive and negative patients (45). Baseline effector protein phosphorylation levels differed predominantly in T cells in Sjögren's patients compared with healthy individuals, with higher p-p38 and p-STAT1 (Y701, S727).…”
Section: Canonical and Non-canonical Signaling In Autoimmune Diseasesmentioning
confidence: 99%
“…Targeting STAT1 may contribute to the treatment of patients with SS. 25 A JAK-1 inhibitor was thought to inhibit IFN-induced transcription genes and B lymphocyte stimulator (BLyS) dominating B-cell differentiation, homeostasis in human salivary glands, as well as regulate IFNα- and IFNγ-induced pSTAT-1 in human salivary gland epithelial cells (SGECs). 26…”
Section: Discussionmentioning
confidence: 99%